Emotional impact of dissection hall on medical students - Singroha, Ritu; Verma, Usha; Malik, Preeti; Chhikara, Pankaj; Yadav, Suman (Asian Journal of Medical Sciences, 2017)
Background: Dissection of the dead human body has been central to medical education since Renaissance. First year medical students normally experience a variety of emotional reactions and mixed feelings, when they encounter human cadavers for the frst time. Aims and Objective: First year medical students normally experience a variety of emotional reactions and mixed feelings, when they encounter human cadavers for the first time. The aim of the study was to study the difference in dissection hall experience of the male and female medical students over a period of time. Material and Methods: Total 178 students were given a questionnaire within 3-4 days and again 3 months after the start of dissection in the dissection hall. The students were asked to answer in either ‘Yes’ or ‘No’ option. Results: All the symptoms were found to be decreased in both male and female students over a period of 3 months except lack of concentration in males. No statistical signifcant difference was found between the symptoms of male and female students. Conclusion: A better teacher – student interaction, pre-education sessions will help in improving the attitudes of students towards cadaveric dissection, thereby reducing the drop-out rates. Asian Journal of Medical Sciences Vol.8(2) 2017 86-89